Formal Methods: 26th International Symposium, FM 2024, Milan, Italy, September 9–13, 2024, Proceedings, Part I - Platzer, André; Rozier, Kristin Yvonne; Pradella, Matteo; Rossi, Matteo (Lecture Notes in Computer Science, 2025)
The open access book set LNCS 14933 + 14934 constitutes the refereed proceedings of the 26th International Symposium on Formal Methods, FM 2024, which took place in Milan, Italy, in September 2024. The 51 full and 4 short papers included in these proceedings were carefully reviewed and selected from 219 submissions. They also include 2 invited talks in full paper length and 10 tutorial papers. The contributions were organized in topical sections as follows: Part I: Invited papers; fundamentals of formal verification; foundations; learn and repair; programming languages.- logic and automata; Part II: Tools and case studies; embedded systems track; industry day track; tutorial papers.